Thermochemical Laser-Induced Periodic Surface Structures Formation by Femtosecond Laser on Hf Thin Films in Air and Vacuum - Dmitrij A. Belousov (MDPI AG, 2021)
Thermochemical laser-induced periodic surface structures (TLIPSS) are a relatively new type of periodic structures formed in the focal area of linear polarized laser radiation by the thermally stimulated reaction of oxidation. The high regularity of the structures and the possibility of forming high-ordered structures over a large area open up possibilities for the practical application for changing the optical and physical properties of materials surface. Since the mechanism of formation of these structures is based on a chemical oxidation reaction, an intriguing question involves the influence of air pressure on the quality of structure formation. This paper presents the results on the TLIPSS formation on a thin hafnium film with fs IR laser radiation at various ambient air pressures from 4 Torr to 760 Torr. Despite the decrease in the oxygen content in the ambient environment by two orders of magnitude, the formation of high-ordered TLIPSS (dispersion in the LIPSS orientation angle δθ < 5°) with a period of ≈700 nm occurs within a wide range of parameters variation (laser power, scanning speed). This behavior of TLIPSS formation is in agreement with experimental data obtained earlier on the study of the kinetics of high-temperature oxidation of hafnium at various oxygen pressures.